Abundant Lewis acidic sites of peculiar fibrous silica zeolite X enhanced toluene conversion in side chain toluene methylation. (1st December 2021) - Aziz, M.A.H; Jalil, A.A; Siang, T.J; Hussain, I.; Rahman, A.F.A; Hamdan, H.
Graphical abstract: Highlights: Ideal Lewis acid sites and basic sites in FZX enhanced catalytic activity. Higher Lewis acid originated from extra-framework enhanced toluene adsorption. FZX catalysts produced 16-fold styrene and ethylbenzene yield compared to CZX. Altering the reaction condition gives different product distributions. In-situ FTIR and kinetic studies revealed the mechanism of SCTM reaction over FZX. Abstract: Side chain toluene methylation reaction (SCTM) is a reliable reaction to produce styrene and ethylbenzene from toluene. Nevertheless, due to the lack of efficient catalyst caused by less Lewis acid sites and mesoporosity properties, the challenges in this SCTM reaction are still ongoing. Hence, this work is accomplished to gain a better understanding in designing a robust catalyst for side chain toluene methylation. Herein, this work emphasizes the uniqueness of top-notch metal-free fibrous silica zeolite X (FZX) by microemulsion method. This FZX showed superior catalytic activity towards side chain methylation with 15.9% yield of styrene and ethylbenzene, which was 16-fold higher compared to the commercial zeolite X (CZX) catalyst. This was achieved by the excellent properties of dendrimeric silica fibers of FZX possessing high concentration of basic sites and Lewis acid sites as well as high mesoporosity, as proved by the FTIR-Pyrrole, FTR-Pyridine and nitrogen physisorption analyses respectively. The presence of intermediates was confirmed by in-situ FTIR toluene-methanol. 27 Al MAS NMR analysis proved that the presence of excessive extraframework alumina (EFAl) species could act as additional Lewis acid sites in FZX to enhance toluene adsorption on the FZX catalyst, thus improving the toluene conversion and desired styrene and ethylbenzene products. Silica MCM41 exhibited lower yield of styrene and ethylbenzene by the fact imbalance of acid base property of catalyst. The kinetic study proved that the side chain toluene methylation occurred via dissimilar dual site mechanism of Langmuir-Hinshelwood. This rationally designed metal-free FZX demonstrates its high potential in polymer and/or petrochemical as well as other industrial applications.